LIQUID DISCIPLESHIP BAGI GENERASI MUDA BERDASARKAN EKKLESIOLOGI CAIR GUNA PENGGENAPAN PENTAKOSTA KETIGA - Meitha Sartika; Gabriel Ravena (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2022)
The third Pentecost emphasizes the revival of young people in the power of the Holy Spirit to fulfill the Great Commission. Unfortunately, today's young generation has lost their passion for the church because the church is no longer relevant. For this reason, we try to propose a liquid discipleship method for the younger generation based on the Liquid Ecclesiology theory by Pete Ward. This research use literature study and constructive theological approach. This article concludes that the characteristics of liquid discipleship on the basis of Liquid Ecclesiology have answers to the characteristics and spirituality of today's young generation that are different from previous generations. Liquid discipleship can be a bridge between the church and the younger generation. In the end, the younger generation can be discipled and sent to make disciples again in order to fulfill the Great Commission as the purpose of the third Pentecost.